Micronutrient content and accumulation in leaves and bunches of black pepper during two crop cycles - Rodrigues Dalazen, Jéssica; Pereira Valani, Gustavo; Gontijo, Ivoney; Machado Dias, Jairo Rafael; Partelli, Fábio Luiz (Revista Ceres, 2022)
A comprehensive knowledge about micronutrient dynamics in leaves and bunches of black pepper is needed in order to proper diagnose nutrient needs, and thus facilitate fertilization management. This study aimed to evaluate micronutrient concentration and accumulation in leaves and bunches of black pepper bunches to understand the crop nutritional demand. The experiment was carried out on in a commercial field of Piper nigrum ‘Bragantina’ located in São Mateus, Espírito Santo, Brazil. Composite samples of leaves and bunches were taken periodically during two crop cycles and the concentration of Fe, Zn, Mn, Cu, and B were assessed. The micronutrient accumulation curves behaved linearly and quadratically, reaching the maximum accumulation point during the time of harvesting. Fe, Mn and B were the micronutrients with highest concentration in both bunches and leaves of black pepper. The nutrient concentration in leaf tissues varied seasonally. These results may contribute to a more sustainable agriculture, in which fertilization rates should consider different needs through the crop stage.